Studies on Coordination Chemistry and Antibacterial Activity of Bidentate NS Schiff Base Derived From SBDTC and 4-Benzyloxybenzaldehyde - Islam, M. H.; Sheikh, M. C.; Islam, M. A. A. A A. (Journal of Scientific Research, 2019)
The condensation of 4-benzyloxybenzaldehyde with S-benzyl dithiocarbazate (SBDTC) in absolute ethanol afforded the Schiff base, S-benzyl-β-N-(4-benzyloxyphenyl)methylene-dithiocarbazate (1). The ligand on further reaction with metal ions in absolute ethanol [for Ni(II), Cu(II), Zn(II)] and in methanol [Pd(II)] resulted in the formation of the corresponding four coordinate complexes. The ligand and its complexes were characterized by physico-chemical techniques, viz., molar conductance, magnetic susceptibility measurement, IR, NMR and solution UV/Vis spectroscopic techniques. The complexes demonstrated stronger antibacterial activity than the free ligand indicating that coordination with these metal ions has enhanced biological potential of the ligand. All the compounds exhibited more or less moderate activity against the test organisms.